Representação e prática dos assistentes sociais que atuam nas escolas Salesianas Paulistas: sujeitos coletivos que se forjam na identificação do projeto profissional - Faermann, Lindamar Alves (2007)
This dissertation thesis is the result of a qualitative research performed concerning Social Workers who deal with philanthropic schools of the Congregação Salesiana , supported by Filhas de Maria Auxiliadora and linked to Inspetoria Santa Catarina de Sena in São Paulo State. The research is focused on the Social Workers representation related to the Social Work practice in those schools, expressing the challenges which arise due to demands and scholar quotidian situations, having as an analysis axe the professional exercise related to the ethical-political project of this occupation. For its development, the Oral History methodology was used, a privileged resource for the social reality knowledge, with an approach which leads toward the experiences, representations and meanings attributed by the individuals in their livings. The analyses were based in the intellectuals linked to the Marxist tradition; thence using methodological-theoretical references which helped to comprehend the historical process as a movement driven by present contradictions. Seeking the social representations, which mean thoughts, feelings and actions expressing the reality experienced by the Social Workers, characters of this research, social-historical issues were found to compose these representations, recognizing that it is nether loosen nor unrelated to a context but inserted in it. As a text, product of a knowledge forged by several voices, this research brings the individual to the narrative center, which means, the narrator is one of the characters and the history telling is part of the history being told . (PORTELLI, 1997, p. 38). This telling points valuable dimensions to be considered, such as the need to increase the intervention field of the Social Works in those schools, so that it does not remain restricted to a certain programs and bureaucratic activities, targeting to overcome focused and specific practices which persist sometimes. It is also clear in their statements that the scholar organization remains centered in some original practices, operating with identities from long time ago; at the same time, the statements reflect the desire of overcome, in tune with the historical moment. Regarding this, distinguishes the importance of examine the Education and the Social Work as an unconditional social right. Recognizes facing the challenges and demands which arises from the scholar quotidian the need of the interdisciplinary work and suggest fecund proposals such as school involvement with the community, the family, the students and the socialpreventive projects development. Constitute itself a qualified field to interfere in the social issues present in the scholar quotidian, the Social Work points the social rights as a focus of its work, as a fight banner and a professional horizon. Still remain implicit in the Social Workers statements the need of rethinking the educative and pedagogical conceptions and the possibility to build new practices, new identities and recreate the professional quotidian. That is the challenge!